227 Diet and Management Strategies to Mitigate Decreased Feed Intake Associated with Terminal Implant Administration in Finishing Beef Steers. (12th April 2022) - Kelly, Alexandria M; Smith, Zachary K; Wright, Cody; Gonda, Michael
Abstract: Terminal implant administration in beef steers often leads to decreased feed intake, leading to less growth. Our objective was to identify diet and management changes that can mitigate this decreased intake. Single-sourced Angus x Simmental steers [n = 27, initial BW = 385.1kg (SD 30.8)] were enrolled in a completely randomized trial to assess the effects of animal movement and dietary net energy for gain (NEg) reduction on feed intake. Steers were implanted with Synovex Choice (100 mg trenbolone acetate and 14 mg estradiol benzoate; Zoetis, Parsippany, NJ) and re-implanted 88 d later with Synovex Plus (200 mg trenbolone acetate and 28 mg estradiol benzoate). Steers had been consuming the finishing diet for approximately 88 d at the time of re-implanting. Steers were allocated into 1 of 3 treatment groups: 1) remained on a 1.43 Mcal/kg NEg diet and moved a shorter distance between the pen and working facility (0.43km), 2) remained on a 1.43 Mcal/kg NEg diet and moved a longer distance (1.05km) to simulate movement in a larger feedlot and 3) fed a 1.32 Mcal/kg NEg diet and moved 1.05km between the pen and working facility. Individual feed and water intake was collected with Insentec feeders and waterers. Individual rumination data was collected with SenseHub Beef (AllFlex Livestock Intelligence). There was no significant difference in feed intake among treatments ( P = 0.26) for 14 d after re-implant. There was significant difference in rumination among treatments ( P = 0.03), with treatment 1 having the greatest minutes of rumination overall. Treatment 1 had significantly greater minutes of rumination than Treatment 3 ( P = 0.04) and tended to have greater minutes of rumination than Treatment 2 ( P = 0.08). Decreasing NEg of the diet did not mitigate feed intake depression but travelling a greater distance did negatively impact rumination for 14 d after re-implanting.